A drug repurposing strategy for overcoming human multiple myeloma resistance to standard-of-care treatment - Chroma, Katarina; Skrott, Zdenek; Gursky, Jan; Bacovsky, Jaroslav; Moudry, Pavel; Buchtova, Tereza; Mistrik, Martin; Bartek, Jiri (Cell death & disease, 2022)
Despite several approved therapeutic modalities, multiple myeloma (MM) remains an incurable blood malignancy and only a small fraction of patients achieves prolonged disease control. The common anti-MM treatment targets proteasome with specific inhibitors (PI). The resulting interference with protein degradation is particularly toxic to MM cells as they typically accumulate large amounts of toxic proteins. However, MM cells often acquire resistance to PIs through aberrant expression or mutations of proteasome subunits such as PSMB5, resulting in disease recurrence and further treatment failure. Here we propose CuET-a proteasome-like inhibitor agent that is spontaneously formed in-vivo and in-vitro from the approved alcohol-abuse drug disulfiram (DSF), as a readily available treatment effective against diverse resistant forms of MM. We show that CuET efficiently kills also resistant MM cells adapted to proliferate under exposure to common anti-myeloma drugs such as bortezomib and carfilzomib used as the first-line therapy, as well as to other experimental drugs targeting protein degradation upstream of the proteasome. Furthermore, CuET can overcome also the adaptation mechanism based on reduced proteasome load, another clinically relevant form of treatment resistance. Data obtained from experimental treatment-resistant cellular models of human MM are further corroborated using rather unique advanced cytotoxicity experiments on myeloma and normal blood cells obtained from fresh patient biopsies including newly diagnosed as well as relapsed and treatment-resistant MM. Overall our findings suggest that disulfiram repurposing particularly if combined with copper supplementation may offer a promising and readily available treatment option for patients suffering from relapsed and/or therapy-resistant multiple myeloma.
Keywords: nádorové buněčné linie; Multiple Myeloma; lidé; Bortezomib; Proteasome Endopeptidase Complex; Proteasome Inhibitors; Drug Repositioning; Neoplasm Recurrence, Local; Cell Line, Tumor; proteasomový endopeptidasový komplex; přehodnocení terapeutických indikací léčivého přípravku; lokální recidiva nádoru; Antineoplastic Agents; chemorezistence; mnohočetný myelom; protinádorové látky; bortezomib; Humans; inhibitory proteasomu; Disulfiram; disulfiram; Drug Resistance, Neoplasm